2007
DOI: 10.1021/ja071268u
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Suppression of 3-/4-Functionalized Benzynes Using Zinc Ate Base (TMP−Zn−ate):  New Approaches to Multisubstituted Benzenes

Abstract: We present full details of our new methods for preparing functionalized benzynes with lithium di-alkyl(2,2,6,6-tetramethylpiperidino)zincate (R2Zn(TMP)Li) through deprotonative zincation as a key reaction. In this system, by choosing appropriate ligands for the zincate, either regioselective zincation of functionalized haloaromatics or the generation of substituted benzynes can be controlled in good yields with excellent chemoselectivity, using the same substrate. Zincation with (t)Bu2Zn(TMP)Li followed by ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(51 citation statements)
references
References 22 publications
2
47
2
Order By: Relevance
“…Thus, the stability of the Ni(0)-ate complex appears to be mainly determined by the σ-donation ability of the organometallic nucleophiles R- [M]. In our previous reports, we have found that in organozincates [77][78][79][80][81][82][83][84][85] the anionic character of C-Zn bond could be drastically enhanced (Table 1 85) ). …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the stability of the Ni(0)-ate complex appears to be mainly determined by the σ-donation ability of the organometallic nucleophiles R- [M]. In our previous reports, we have found that in organozincates [77][78][79][80][81][82][83][84][85] the anionic character of C-Zn bond could be drastically enhanced (Table 1 85) ). …”
Section: Resultsmentioning
confidence: 99%
“…Thus novel classes of metallating agents resulting from various combinations of organometallic compounds with alkali, including various ate complexes, have been designed, such as zincates (R 2 Zn(TMP)Li·TMEDA) [34] ((TMP) 2 Zn·2MgCl 2 ·2LiCl) [5], magnesates ((TMP) 3 MgLi, Bu 2 (TMP)MgLi, Bu(TMP) 2 MgLi, (TMP) 4 MgLi 2 ) [3,6], aluminates (iBu 3 Al(TMP)Li, Al(TMP) 3 ·3LiCl) [3,7], manganate ((Me 3 SiCH 2 ) 2 Mn(TMP)Li·TMEDA) [3,8], cuprates (MeCu(TMP)(CN)Li 2 , (TMP) 2 CuLi) [910] and cadmium amides ((TMP) 3 CdLi) [1112], for regio- and/or chemoselective deprotonative metalation of aromatics, producing arylmetal intermediates under smooth reaction conditions that are directly suitable for electrophilic reactions as well as transition-metal-catalyzed cross-coupling reactions. By contrast, the methodology for transition-metal-catalyzed direct arylation [1318] is based upon the use of various catalytic metalation processes, such as electrophilic metalation, oxidative addition, halogen- or base-assisted metalation–deprotonation, and carbometalation [1922] combined with diverse functionalizing agents, such as alkenes and alkynes [23], oxidants [24], nucleophiles, organometallics and arenes [2526] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…10 In order to seek more efficient and direct methods for introducing functionalities into heteroaromatic rings, we focused the deprotonative 65 metalation using the corresponding mixture with cadmium instead of zinc on the difference of metal size. First attempts using anisole (1a) as substrate indicated that an in situ prepared mixture of CdCl 2 ·TMEDA 11 (0.5 equiv) and LiTMP (1.5 equiv) was suitable for an efficient reaction, when used in 70 THF at room temperature.…”
mentioning
confidence: 99%